Application of Neutron Computed Tomography in Enhanced Oil Recovery for Analysing Oil Distribution in Berea Sandstone using Bagasse Surfactant (Rudarsko-geološko-naftni zbornik, 2023)
The Neutron Computed Tomography (NCT) technique was adopted to study oil content within sandstone. In recent times, oil industries have turned to the Enhanced Oil Recovery (EOR) technique that uses chemicals/surfactants to reduce interfacial tension to maximize oil production from mature oil fields. The Berea core played a crucial role in investigating surfactant effectiveness for liberating trapped oil. The presented research is based on laboratory experiments carried out at the National Research and Innovation Agency and at the Trisakti University, Indonesia. The research proceeded in three steps. The first step was observation on the Berea core that is saturated with a low salinity brine of 40,000 ppm and 60,000 ppm and assessment of the total porosity of the sandstone. The second step included injecting oil into the sample and examining the water distribution. The final step was to inject sugarcane bagasse surfactant with 2% surfactant concentration to extract oil from the sandstone, then it was subjected to NCT analysis. The observations show that the pores are evenly distributed in the middle, the oil content accumulates at the edge, almost no oil remains in the middle of the Berea core after water injection, and the remaining oil returns to the main flow after surfactant injection. The results show that oil movement in the Berea core with 40,000 ppm salinity is better than oil movement with 60,000 ppm. The salinity of the brine can affect the mobility of oil droplets in the Berea core, and surfactant injection processes have better performance at lower salinity and are susceptible to higher salinity.